Selective dissolution-based solvent treatment perovskite solar cell and preparation method thereof

The treatment of perovskite films through selectively dissolved solvents solves the challenges of perovskite solar cells in long-term stability and commercial applications, and achieves the effect of improving photoelectric performance and stability.

CN119789661APending Publication Date: 2025-04-08SUZHOU UNIV OF SCI & TECH

Patent Information

Application Number
CN202411767036.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Perovskite solar cells have challenges in long-term stability and commercial applications, mainly due to their chemical instability, environmental sensitivity and the degradation behavior of devices under light.

Method used

The perovskite film is treated with a selectively dissolved solvent, and the unreacted substances remaining on the surface are selectively removed, the film quality is improved, the surface defects are passivated, and the secondary crystal growth is promoted, and the interface contact between the perovskite layer and the hole transport layer is optimized.

Benefits of technology

It improves the photoelectric performance and stability of perovskite solar cells, reduces defects at the surface and interface, and extends the service life of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119789661A_ABST
    Figure CN119789661A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solar cell preparation, and particularly relates to a perovskite solar cell based on selective dissolution solvent treatment and a preparation method thereof. The perovskite cell comprises a conductive substrate, an electron transport layer, a perovskite light absorption layer, a hole transport layer and a metal electrode which are arranged in sequence. A solvent with a selective dissolution characteristic is prepared on the perovskite light absorption layer, and passivation modification is carried out on the perovskite thin film. The invention provides a simple perovskite thin film processing method, complex molecular engineering is not needed, the solvent-based processing effectively passivates the defects of the thin film, improves the quality of the perovskite thin film, establishes a new built-in electric field, forms a more appropriate energy band structure, reduces the recombination of charge carriers, and improves the performance of the perovskite thin film. The separation and transmission capabilities of holes at the surface interface are accelerated, so that the photoelectric property of the perovskite cell is optimized, and the stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cell preparation, and in particular relates to a perovskite solar cell treated with a solvent based on selective dissolution and a preparation method thereof. Background Art

[0002] Perovskite SolarCells (PSCs), as an emerging material in the third generation of photovoltaic technology, has attracted widespread attention in recent years due to its excellent optoelectronic properties, low cost and simple preparation process. Perovskite materials have high light absorption coefficients, long charge carrier diffusion distances and adjustable bandgap structures, which give them high potential in photoelectric conversion. From the initial photovoltaic conversion efficiency (PCE) of less than 4% to the current record of breaking 26%, the rapid development of PSCs has demonstrated its potential to become the mainstream technology of the next generation of solar cells.

[0003] However, despite the high efficiency and good performance of perovskite solar cells in the laboratory, their long-term stability remains one of the key challenges hindering their commercial application. The chemical instability of perovskite materials, the sensitivity of the environment to their material properties (such as humidity, oxygen, temperature, etc.), and the degradation behavior of the device under light all limit its long-term service life in the actual environment. Especially in unpackaged devices, perovskite films are easily affected by moisture, causing material decomposition, which in turn affects the efficiency and stability of the battery.

[0004] In the structure of perovskite solar cells, the interface quality between the perovskite layer and its upper and lower interface materials (such as electron transport layer and hole transport layer) is crucial to improving the optoelectronic performance and long-term stability of the device. Grain boundaries, surface defects in the perovskite layer, and residual chemicals on the interface may become traps for charge recombination, reducing the conversion efficiency of the device and accelerating its aging. Therefore, improving the surface quality of perovskite films, passivating surface defects, and optimizing the interface between the perovskite layer and other functional layers have become one of the hot issues in the current research of perovskite solar cells.

[0005] In the prior art, methods for passivating perovskite films include using a variety of chemical reagents or different post-processing techniques to reduce defects and enhance stability. Although these methods can improve the performance of perovskite materials to a certain extent, they generally have problems such as complex operations, the need for expensive or special chemicals, time-consuming and difficult-to-control processing, and are not suitable for large-scale production. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a preparation of a perovskite solar cell based on selective dissolution solvent treatment. The perovskite cell comprises a conductive substrate, an electron transport layer, a perovskite light absorption layer, a passivation layer treated with the above selective dissolution solvent, a hole transport layer and a metal electrode arranged in sequence, the selective dissolution solvent includes but is not limited to isopropyl alcohol, chlorobenzene, etc., and the treatment method includes coating and annealing.

[0007] The solvent treatment time of the selective dissolution characteristic is less than 300 s.

[0008] The present invention utilizes a selectively dissolving solvent to treat a perovskite film, uses the solvent to selectively remove unreacted substances remaining on the surface of the perovskite, improves the film quality and passivates surface defects, promotes secondary crystal growth, reduces defects on the surface and at the interface, and thereby improves the photoelectric performance of the perovskite solar cell.

[0009] The selectively dissolved solvent treated passivation layer of the present invention optimizes the interface contact between the perovskite layer and the hole transport layer, so that the energy bands of each layer are arranged more neatly, thereby effectively reducing the interface charge recombination and improving the stability of the perovskite solar cell.

[0010] The present invention provides a perovskite solar cell treated with a solvent based on selective dissolution, comprising a conductive substrate, an electron transport layer, a perovskite light absorbing layer, a hole transport layer and a metal electrode arranged in sequence; one side of the perovskite light absorbing layer is treated with a solvent with selective dissolution characteristics to form a passivation layer between the perovskite light absorbing layer and the hole transport layer.

[0011] Preferably, the solvent with selective solubility properties is selected from isopropanol or chlorobenzene, and the solvent with selective solubility properties does not require the synthesis of a complex molecular structure.

[0012] Preferably, the thickness of the perovskite light-absorbing layer after being treated with a solvent having selective dissolving properties is 400-500 nm.

[0013] Preferably, the processing time of the solvent with selective dissolving properties is less than 300 s.

[0014] Preferably, the selective dissolving solvent treatment is followed by annealing at a temperature below 150°C.

[0015] Preferably, the conductive substrate is selected from fluorine-doped tin oxide glass (FTO) or indium tin oxide conductive glass (ITO).

[0016] The present invention also provides a method for preparing the above-mentioned perovskite solar cell based on selective dissolution solvent treatment, comprising the following steps:

[0017] S1: coating an electron transport material on a conductive substrate to form an electron transport layer; the conductive substrate is selected from a semiconductor material;

[0018] S2: coating a perovskite precursor solvent on the surface of the electron transport layer, and annealing to form a perovskite light absorbing layer;

[0019] S3: preparing a selectively dissolved solvent-treated passivation layer on the surface of the perovskite light-absorbing layer, and coating a hole transport material on the surface of the passivation layer to form a hole transport layer;

[0020] S4: preparing a metal electrode on the surface of the hole transport layer to obtain the perovskite solar cell treated with the solvent based on selective dissolution.

[0021] Preferably, the semiconductor material is selected from conductive glass or silicon wafer.

[0022] Preferably, the perovskite precursor solvent includes lead iodide (PbI2), formamidine hydroiodide (FAI), methylammonium bromide (MABr), methylammonium chloride (MACl) and cesium iodide.

[0023] Furthermore, lead iodide is dissolved using dimethylformamide and dimethyl sulfoxide.

[0024] Preferably, in step S2, the annealing time is 150-155° C. and the time is 20-30 min.

[0025] Preferably, in step S1, tin oxide nanoparticles are dispersed in water to obtain a tin oxide precursor solution as an electron transport material, the tin oxide precursor solution is coated on a conductive substrate, and annealing is performed to obtain the electron transport layer.

[0026] Furthermore, the particle size of the tin oxide nanoparticles is 1-10 nm, and the concentration of the tin oxide nanoparticles in the tin oxide precursor solution is 100-300 mM.

[0027] Preferably, in step S1, the electron transport layer is coated by spin coating at a speed of 2000-5000 rpm.

[0028] Preferably, in step S2, the perovskite light absorbing layer is coated by spin coating at a spin coating speed of 1000-6000 rpm.

[0029] Preferably, in step S3, a spin coating method is used to coat a solvent with selective dissolving characteristics to form a passivation layer, and the spin coating speed is 1000-3000 rpm.

[0030] Preferably, in step S3, the hole transport layer is coated by spin coating at a speed of 1000-2000 rpm.

[0031] Preferably, the material of the hole transport layer is selected from 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), and the thickness of the hole transport layer is 200-300 nm.

[0032] Preferably, in step S4, the metal electrode is a silver electrode or a gold electrode, and the thickness of the metal electrode is 50-150 nm.

[0033] Furthermore, the thickness of the metal electrode is 100 nm.

[0034] Preferably, in step S4, a thermal evaporation instrument is used to evaporate and prepare a metal electrode on the surface of the hole transport layer, the evaporation source is metal, the evaporation rate is 0.7 nm / s, and the evaporation pressure is 1×10 -5 Pa.

[0035] Specifically, the method for preparing a perovskite solar cell based on selective dissolution solvent treatment comprises the following steps:

[0036] S1. Disperse tin oxide nanoparticles in water to obtain a tin oxide nanoparticle dispersion with a concentration of 100-300 mM; use a pipette to absorb the tin oxide precursor solvent and evenly coat it on the surface of the UV-treated conductive substrate, spin-coat it at a rate of 5000 rpm for 30 seconds to obtain a uniform film, place the prepared film sample on a preheated heating table, anneal at 150°C for 20 minutes to remove impurities, and form a tin oxide film with a thickness of 30-80 nm. After the substrate is cooled to room temperature, it is UV-cleaned for 20 minutes;

[0037] S2. dripping a perovskite precursor solvent onto the acidified tin oxide film, and spin coating at a rate of 6000 rpm for 30 seconds; after spin coating for 10 seconds, dripping an anti-solvent anisole, and then annealing in air at 150° C. for 10 minutes to obtain a highly crystallized bright black perovskite film, forming a perovskite light absorbing layer with a thickness of 350-500 nm;

[0038] S3. After cooling to room temperature, spin-coat 50 μL of a selectively dissolving solvent at a rate of 2000 rpm, so that the solvent stays on the surface of the perovskite film for less than 300 s, and then anneal at less than 150° C. for 5 min to form a passivation layer.

[0039] S4. A hole transport layer and a metal electrode are sequentially prepared on the surface of the perovskite light-absorbing layer to obtain a perovskite solar cell.

[0040] It should be further explained that different temperatures and solvent treatment times will have different effects on the performance of the device, and different temperatures and solvent treatment times can reflect the optimization effect of the selective dissolving solvent treatment and the device performance.

[0041] Furthermore, before coating the tin oxide precursor solvent, a step of irradiating the conductive substrate with ultraviolet light is included, in order to increase the hydrophilicity of the film surface, so as to facilitate subsequent spin coating and prepare a uniform and dense film.

[0042] Furthermore, after annealing, the process further includes a step of irradiating the electron transport layer with ultraviolet light after cooling, in order to increase the hydrophilicity of the film surface and facilitate subsequent spin coating to prepare a uniform and dense film.

[0043] Furthermore, steps S1-S4 are all completed in a glove box to isolate the device from the influence of the external environment.

[0044] The technical solution of the present invention has the following advantages over the prior art:

[0045] (1) The present invention adopts a method of treating the perovskite film with a selective dissolving solvent to promote the secondary growth of the grains.

[0046] (2) The method of treating perovskite thin films with selective dissolving solvents of the present invention optimizes surface defects, accelerates the separation and transmission capacity of holes at the surface interface, optimizes the energy level arrangement, and thus optimizes the photoelectric performance of perovskite solar cells.

[0047] (3) The method of treating the perovskite film with a selectively dissolving solvent of the present invention can maintain relatively high photoelectric performance after long-term storage, thereby greatly improving the stability of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 is a scanning electron microscope image of the perovskite film prepared in Example 1 of the present invention after passivation treatment with isopropanol, a solvent having selective dissolution;

[0049] Figure 2 is a scanning electron microscope image of a perovskite film prepared in Comparative Example 1 of the present invention that has not been passivated with a solvent having selective dissolution;

[0050] Figure 3 This is a scanning electron microscope image of the perovskite film prepared in Example 2 of the present invention after passivation treatment with chlorobenzene, a solvent having selective dissolution

[0051] Figure 4 1 is a JV curve of the perovskite battery prepared in Example 1 of the present invention and Comparative Example 1;

[0052] Figure 5It is a schematic diagram of the normalized photoelectric conversion efficiency of the perovskite cells prepared in Example 1 of the present invention and Comparative Example 1 under continuous illumination;

[0053] Figure 6 1 is the efficiency distribution diagram of the perovskite cells prepared in Example 1 of the present invention and Comparative Example 1;

[0054] Figure 7 It is a JV curve diagram of the perovskite cells prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0055] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0056] Example 1

[0057] S1. Disperse 15% tin oxide nanoparticle colloidal dispersion in deionized water to obtain a tin oxide nanoparticle dispersion with a volume ratio of 1:7. Disperse the obtained tin oxide nanoparticles by ultrasonic for 25 minutes. Use a pipette to draw 50 μL of tin oxide nanoparticle precursor solvent and evenly coat it on the UV-treated ITO conductive glass surface. Spin coat at a rate of 5000 r / min for 30 seconds to obtain a uniform film. Place the prepared film sample on a preheated heating table and anneal at 150°C for 30 minutes to form a tin oxide film with a thickness of about 50 nm. After the substrate cools to room temperature, clean it with UV for 30 minutes.

[0058] S2. Weigh 736 mg of lead iodide (PbI2), 224 mg of formamidine hydroiodide (FAI), 16.2 mg of methylammonium bromide (MABr), 20 mg of methylammonium chloride (MACl), and 19.8 mg of cesium iodide (CsI) respectively, stir evenly at room temperature for 1 hour, and prepare a light yellow perovskite precursor solvent; take 50 μL of the perovskite precursor solvent and drop it on the tin oxide film, and spin-coat it at a rate of 6000 r / min for 30 seconds; after spin-coating for 10 seconds, add 200 μL of anti-solvent anisole, and then anneal in air at 150°C for 10 minutes to obtain a highly crystalline bright black perovskite film with a thickness of about 400 nm;

[0059] S3. After cooling to room temperature, spin-coat 50 μL of isopropanol, a selective solvent, at a rate of 2000 r / min, so that the isopropanol stays on the surface of the perovskite film for less than 300 s, and then anneal at less than 150° C. for 5 min to form a passivation layer.

[0060] S4. After cooling to room temperature, 25 μL of Spiro-OMeTAD, a hole transport layer material, was dynamically spin-coated at a rate of 2000 r / min to a thickness of 250 nm. The substrate was then transferred to a thermal evaporation instrument and a 100 nm thick silver electrode was evaporated at an evaporation rate of 0.7 nm / s. The evaporation source was silver and the evaporation pressure was 1×10 -5 Pa.

[0061] According to the above steps, a perovskite solar cell is prepared, which includes, from bottom to top: a transparent conductive substrate, an electron transport layer, a perovskite light absorbing layer, a passivation layer, a hole transport layer and a metal electrode. The transparent conductive substrate is made of indium tin oxide conductive glass (ITO), and the electron transport layer is made of tin oxide film.

[0062] Example 2

[0063] The perovskite solar cell was prepared according to the method of Example 1, except that the selectively dissolving solvent isopropanol was replaced by chlorobenzene.

[0064] Comparative Example 1

[0065] A perovskite solar cell was prepared according to the method of Example 1, except that the perovskite film was not passivated.

[0066] Comparative Example 2

[0067] A perovskite solar cell was prepared according to the method of Example 1, except that the selectively dissolving solvent isopropanol was replaced with the two-dimensional material black phosphorus.

[0068] Comparative Example 3

[0069] The perovskite solar cell was prepared according to the method of Example 1, except that the selectively dissolving solvent isopropyl alcohol was replaced with phenethylammonium iodide.

[0070] Effect evaluation of perovskite battery photoelectric performance test

[0071] (1) SEM tests were performed on the perovskite film prepared in Example 1 after passivation treatment with isopropanol, a solvent having selective dissolution, and the perovskite film prepared in Comparative Example 1 without passivation treatment with isopropanol, a solvent having selective dissolution. The results are as follows: Figure 1 , Figure 2 shown.

[0072] Figure 1 , Figure 2 In contrast, in Example 1 of the present invention, small grains that promote the secondary growth of the perovskite film are generated at the surface interface of the perovskite film after passivation treatment with isopropanol, a solvent with selective dissolution, and there are no obvious defects on the surface of the film. Figure 3The perovskite film passivated by chlorobenzene treatment has no obvious holes or gaps.

[0073] (2) The JV curves of the perovskite cells prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 4 shown.

[0074] Figure 4 Display, at 100mW / cm 2 Under simulated sunlight, the perovskite solar cell composed of perovskite thin film treated with selective solvent isopropanol has an open circuit voltage of 1.16V and a short circuit current density of 24.84mA / cm 2 , the filling factor is 80.78, and the highest photoelectric conversion efficiency is 23.34%.

[0075] The photoelectric conversion efficiency of the perovskite cells prepared in Example 1 and Comparative Example 1 under continuous illumination was tested, and the normalized photoelectric conversion efficiency diagram is shown in Figure 5 .

[0076] from Figure 5 It can be found that under 1000h of illumination, the photoelectric conversion efficiency of the perovskite cell composed of the perovskite film treated with the selective solvent isopropanol only decreased by 8%, and its stability was significantly improved compared with Comparative Example 1. The results show that the isopropanol solvent treatment reduces the defects in the perovskite film and increases the carrier transfer rate, thereby improving the performance and stability of the perovskite solar cell composed of the perovskite film treated with the selective solvent isopropanol.

[0077] The efficiency distribution diagram of the perovskite cells prepared in Example 1 and Comparative Example 1 is shown in Figure 6 .

[0078] Figure 6 It is shown that the efficiency distribution of the perovskite cell composed of the perovskite film treated with the selective solvent isopropanol is higher than that of the perovskite cell in Comparative Example 1 that has not been treated with the selective solvent, indicating that the perovskite cell prepared in Example 1 has good repeatability.

[0079] (3) The JV curves of the perovskite cells prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown in FIG. Figure 7 shown.

[0080] Figure 7 It shows that perovskite cells composed of perovskite films treated with selective solvents have good photoelectric properties.

[0081] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A perovskite solar cell based on selective dissolution solvent treatment, characterized in that The invention comprises a conductive substrate, an electron transport layer, a perovskite light absorbing layer, a hole transport layer and a metal electrode which are arranged in sequence; one side of the perovskite light absorbing layer is treated with a solvent having selective dissolving properties to form a passivation layer between the perovskite light absorbing layer and the hole transport layer.

2. The perovskite solar cell based on selective dissolution solvent treatment according to claim 1, characterized in that: The solvent with selective dissolving properties is selected from isopropyl alcohol or chlorobenzene.

3. The perovskite solar cell based on selective dissolution solvent treatment according to claim 1, characterized in that: The thickness of the perovskite light-absorbing layer after being treated with a solvent having selective dissolution characteristics is 400-500 nm.

4. The perovskite solar cell based on selective dissolution solvent treatment according to claim 1, characterized in that: The processing time of the solvent with selective dissolving properties is less than 300 seconds.

5. The perovskite solar cell based on selective dissolution solvent treatment according to claim 1, characterized in that: The selective dissolving characteristic solvent treatment is followed by annealing at a temperature below 150°C.

6. The perovskite solar cell based on selective dissolution solvent treatment according to claim 1, characterized in that: The conductive substrate is selected from fluorine-doped tin oxide glass or indium tin oxide conductive glass.

7. A method for preparing a perovskite solar cell based on selective dissolution solvent treatment according to any one of claims 1 to 6, characterized in that: The steps include: S1: coating an electron transport material on a conductive substrate to form an electron transport layer; the conductive substrate is selected from a semiconductor material; S2: coating a perovskite precursor solvent on the surface of the electron transport layer, and annealing to form a perovskite light absorbing layer; S3: preparing a selectively dissolved solvent-treated passivation layer on the surface of the perovskite light-absorbing layer, and coating a hole transport material on the surface of the passivation layer to form a hole transport layer; S4: preparing a metal electrode on the surface of the hole transport layer to obtain the perovskite solar cell treated with the solvent based on selective dissolution.

8. The preparation method according to claim 7, characterized in that: The semiconductor material is selected from conductive glass or silicon wafer.

9. The preparation method according to claim 7, characterized in that: The perovskite precursor solvent includes lead iodide, formamidine hydroiodide, methylammonium bromide, methylammonium chloride and cesium iodide.

10. The preparation method according to claim 7, characterized in that: In step S2, the annealing time is 150-155° C. for 20-30 minutes.

Citation Information

Patent Citations

  • Preparation method of solar cell with surface passivated perovskite thin film

    CN108807675A

  • Method for preparing perovskite absorption layer by adopting two-step method and perovskite solar cell

    CN110364629A

  • Perovskite solar cell and preparation method thereof

    CN114864829A

Cited By

  • Preparation method of passivation layer, perovskite crystalline silicon laminated cell and manufacturing method thereof

    CN121174898A